2000
DOI: 10.1063/1.1324697
|View full text |Cite
|
Sign up to set email alerts
|

F + and F centers in α-Al2O3 by electron-induced x-ray emission spectroscopy and cathodoluminescence

Abstract: Study of an α-Al2O3 single crystal by electron-induced x-ray emission spectroscopy and cathodoluminescence is reported. The relative intensities of optical emissions due to F+ and F centers have been determined as a function of the parameters of the electron beam and the annealing of the sample. It is shown that the F+ centers, i.e., the oxygen vacancies with one trapped electron, are predominant when the density of the incident electron beam increases. Similar variation is observed when the electron energy va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Pure sapphire is colorless and does not show any luminescence at all, but impurities even at concentrations of a few parts per million can cause a remarkable luminescence giving rise to color centers. These color centers or defects can be induced by ion bombardment [3]. Defects induced in sapphire may be various kinds; single vacancy centers (F and F + ) and dimmers (F 2 , F 2+ and F 2 2+ centers) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pure sapphire is colorless and does not show any luminescence at all, but impurities even at concentrations of a few parts per million can cause a remarkable luminescence giving rise to color centers. These color centers or defects can be induced by ion bombardment [3]. Defects induced in sapphire may be various kinds; single vacancy centers (F and F + ) and dimmers (F 2 , F 2+ and F 2 2+ centers) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among these particle beams, the electron beam is the most convenient one. However, it is known that electron beam irradiations to sapphire can change oxygen vacancies to F + and F centers, which are common luminescence centers in various oxide materials composed of oxygen vacancies with one trapped electron and two captured electrons, respectively [10,11]. In previous studies, we have found that such electron-irradiation-induced behaviors substantially depend on the type of the sapphire and crystalline quality [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, a CL spectrum of ¡-Al 2 O 3 reported by P. Jonnard et al 5) was shown in the inset of the figure in which the solid and dashed lines were induced by 4 keV electron beam irradiation with electron fluxes of 9.4 © 10 19 and 9.4 © 10 18 electrons/m 2 ·s, respectively. The present CL spectrum is composed of intense line emission at 690 nm (1.8 eV) accompanying a few satellite peaks and a broad band emission peaked at 330 nm (3.8 eV).…”
Section: Rapid Publicationmentioning
confidence: 99%
“…In the observed spectra, no emission of F center (oxygen vacancy trapping two electrons) at around 410 nm (3.0 eV) appeared. 5) In general, CL spectra for Al 2 O 3 show double band emissions attributed to F and F + centers. Such double band emissions, in particular, the intensity ratio of F + /F emission changed with the flux and the fluence as shown in the inset of Fig.…”
Section: Rapid Publicationmentioning
confidence: 99%